(untitled) (Libellarium: journal for research in the field of information and related sciences, 2018)
The aim of the paper, based on selected literature, is to offer a brief comprehensive overview of the development of Croatian musical art from the medieval period to the 20th century. Such an overview approach provides a clear insight into the basic development trends and influences of Croatian music, but also into the ways of its integration into the world heritage of musical values. It also highlights the historical and political circumstances that influenced musical development. Furthermore, the paper enables a comparison of the influence of historical circumstances on the development of Croatian musical art in various historical periods. The selection of literature generally guided the author in the preparation of this review and in the complex process of research on selected topics with the aim of creating a brief summary of the mentioned issues.